Speaking Out: Complex Trauma Survivors on Trauma-Informed Practice for Open/Online Higher Education - Schmidt, Hilary (International Journal of E-Learning & Distance Education / Revue internationale de l’apprentissage en ligne et de l’enseignement à distance, 2026)
Childhood complex trauma profoundly disrupts survivors’ lifetime educational and career trajectories, sharply reducing the odds of credential completion and adult employment. Ensuring survivors have every opportunity to access and complete higher education is an essential step toward equity, and open and online learning provides one possible pathway. Nonetheless, prior educational research has largely neglected survivors’ perspectives regarding their own needs, contradicting the key principle of collaboration within a trauma-informed approach. In response to this gap, this paper explores survivors’ needs through their own eyes as they learn in an open and online postsecondary setting. Findings from this small qualitative case study include the high value survivors place on access, self-advocacy, and assistance from advisors and others in the university system. The findings also highlight challenges around communication and interaction, both within courses and more broadly at the institutional level, and survivors’ desire for the university to prioritize safety, trust, transparency, empowerment, voice, and choice, key elements of established trauma-informed practice. Implications include the need for further survivor-centred research and the importance of systemic, pan-institutional approaches to trauma-informed educational practices in open/online postsecondary contexts.